MicroRNA Techniques: Valuable Tools for Agronomic Trait Analyses and Breeding in Rice - Chen, Jiwei; Teotia, Sachin; Lan, Ting; Tang, Guiliang (Frontiers in Plant Science, 2021)
MicroRNAs (miRNAs) are a class of small noncoding RNAs that regulate gene expression at the posttranscriptional level. Extensive studies have revealed that miRNAs have critical functions in plant growth, development, and stress responses and may provide valuable genetic resources for plant breeding research. We herein reviewed the development, mechanisms and characteristics of miRNA techniques while highlighting a widely used approaches, namely, the short tandem target mimic (STTM) approach. We described STTM-based advances in plant science, especially in the model crop rice, and introduced the CRISPR-based transgene-free crop breeding. Finally, we discussed the challenges of and unique opportunities for combining STTM and CRISPR technology for crop improvement and agriculture.